2000
DOI: 10.1002/1097-0185(20000701)259:3<334::aid-ar100>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Calbindin D28k and parvalbumin immunoreactivity in the rabbit superior colliculus: An anatomical study

Abstract: The expression pattern of two calcium binding proteins (CaBP), calbindin D28k (CB) and parvalbumin (PV), in the superior colliculus (SC) of the adult rabbit, as well as the morphology of the immunoreactive cells were examined. The study was performed on 12 rabbits. Coronal sections from postmortem SC were analyzed by light microscopy, and drawings of CaBP‐labeled cells were obtained using a drawing tube. No previous information is available on either the CB/PV expression or the morphology of CB/PV positive cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 57 publications
(85 reference statements)
4
5
0
1
Order By: Relevance
“…We have found that PSA‐NCAM is present in the superficial retinal recipient layers, as previously described (Murphy et al, ), but its expression was not affected by the visual deprivation. Regarding the study of the distribution of PV+ cells, we found them concentrated in the superficial visuosensory layer and distributed sparsely and in patches in the intermediate layers, as previously described (González‐Soriano, González‐Flores, Contreras‐Rodríguez, Rodríguez‐Veiga, & Martínez‐Sainz, ; Villalobos, Wu, Lee, May, & Basso, ). The PV+ expressing cells located in the superficial retinorecipient layers were not surrounded by PNNs, whereas most of those located in deeper layers were enwrapped by these structures.…”
Section: Discussionsupporting
confidence: 82%
“…We have found that PSA‐NCAM is present in the superficial retinal recipient layers, as previously described (Murphy et al, ), but its expression was not affected by the visual deprivation. Regarding the study of the distribution of PV+ cells, we found them concentrated in the superficial visuosensory layer and distributed sparsely and in patches in the intermediate layers, as previously described (González‐Soriano, González‐Flores, Contreras‐Rodríguez, Rodríguez‐Veiga, & Martínez‐Sainz, ; Villalobos, Wu, Lee, May, & Basso, ). The PV+ expressing cells located in the superficial retinorecipient layers were not surrounded by PNNs, whereas most of those located in deeper layers were enwrapped by these structures.…”
Section: Discussionsupporting
confidence: 82%
“…For example, CBs in the cat SC are found within the upper half of the superficial layer, with a second tier bridging the deep OL and IGL, and a third tier within the DGL [43]. Similar results have been found for SCs of monkeys, rabbits, rats, and hamsters [8, 17, 33, 39, 42, 44, 53]. The dog also has 3 tiers of CB-IR cells in the SC, but the distribution of this protein in the superficial SC also differs from that of previously studied animals, as the first tier of CB-IR cells is found in the lower SGL instead of the upper SGL.…”
Section: Discussionmentioning
confidence: 62%
“…However, the distribution pattern of PV-IR cells in the bat SC is similar to that of many other mammalian SCs. In the cat [45], rabbit [17], rat [12], and hamster SC [48], PV-IR cells are concentrated in a tier within the lower SGL and upper OL, while scattered PV-IR cells are found within the deep layers of the SC.…”
Section: Discussionmentioning
confidence: 99%
“…The mammalian superior colliculi form laminated eminences on the rostral half of the tectum of the midbrain. Although studies have established the architecture of the mammalian superior colliculus in different species, notably the rat (Altman & Carpenter, 1961; Brodal, 1972; Harting, 1977; Graybiel, 1978), rabbit (Barker & Dreher, 1998; Gonzalez‐Soriano et al. 2000; McHaffie et al.…”
Section: Introductionmentioning
confidence: 99%